Practical musicology - Thomas, Simon Zagorski- (New York : Bloomsbury Academic, 2022)
"A theoretical framework for studying how music is made as opposed to what is produced"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Musicology; Music -- Performance -- Research